Size-dependent optoelectrical properties of 365 nm ultraviolet light-emitting diodes. (27th September 2019) - Asad, Mohsen; Li, Qing; Sachdev, Manoj; Wong, William S
Abstract: In this paper, the size-dependent optical and electrical properties of 365 nm InGaN/AlGaN ultraviolet micron-size light-emitting diodes ( μ LEDs) on c-plane sapphire substrates is investigated. The series resistance of the μ LED increased from 20 Ω to 15 kΩ when the diameter of the device decreased from 150 to 3 μ m. The ideality factor increased from 4 to 4.6 over the same range of diameters due to the increase in the defect density for the smaller μ LEDs. Moreover, electroluminescence characterization showed a fixed and red-spectral-shift emission for the μ LEDs with diameters smaller than 10 μ m and larger than 15 μ m, respectively. The red-shift was due to band-gap narrowing in InGaN/AlGaN multi-quantum wells as a result of self-heating at higher current densities in the larger diameter μ LEDs. Due to an increase in the heat dissipation of devices with a high surface to volume ratio, the smaller diameter devices were found to have higher light extraction efficiency and no measurable emission spectrum shift.